PARENTING, ISLAMIC MORALS AND OBEDIENCE - Yuarini Wahyu Pertiwi; Amirul Muminin (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aims to measure someone’s obedience which is influenced by the Islamic morals and parenting. Parenting in this study refers to Authoritarian, Permissive and Democratic. While Islamic morals in this study are related to rules and conventions regarding what humans should do in their interactions with others. Respondent of this study was 120 people using accindental sampling. Aiken V validity and Alpha Cronbach reliability is used to measure Obedience Scale (0.764, 0.849), Islamic Moral scale (0.830, 0.804), Authoritarian scale (0.917, 0.611), Permissive Scale (0.833, 0.543) and Demokratic Scale (0.850, 0.891). There is a significant correlation between Obedience and Islamic morals (p= .521), obedience and democratic parenting (p = .380), Democratic parenting and Islamic morals (p= .636). Regression analysis was carried out to see the influence and contribution of Islamic morals and parenting authoritarian, permissive and democratic – towards obedience, where Islamic morals significantly affected compliance by 27.1% and democratic parenting by 14.4%.